2016
DOI: 10.4236/aim.2016.67054
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Urinary Tract Infections (UTI) amongst Patients Attending Primary Health Centres in Anambra State

Abstract: Urinary tract infections (UTIs) are one of the most prevalent extra-intestinal bacterial infections. It is a common disease encountered in medical practice affecting people of all ages, from neonate to geriatric age group. These infections are on the increase for outpatients attending Primary Health Centres in Anambra State, Nigeria, therefore the need for this study. The prevalence rate of urinary tract infection, age distribution and influence of sex were determined. Susceptibility pattern of the infectious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
2
6
2
Order By: Relevance
“…The observations with gram-negative bacteria have the highest sensitivity to Gentamycin after nitrofurantoin made by Kenechukwu et al 40 are in line with our findings. Gentamycin is an aminoglycoside antibiotic that works by inhibiting protein synthesis, thereby preventing bacteria survival and multiplication.…”
Section: Discussionsupporting
confidence: 82%
“…The observations with gram-negative bacteria have the highest sensitivity to Gentamycin after nitrofurantoin made by Kenechukwu et al 40 are in line with our findings. Gentamycin is an aminoglycoside antibiotic that works by inhibiting protein synthesis, thereby preventing bacteria survival and multiplication.…”
Section: Discussionsupporting
confidence: 82%
“…They observed that all strains tested were susceptible to chloramphenicol. Contrary to our result [49], reported high resistance of Escherichia coli to antibiotics. However [50], noted that bacterial isolates from fish ponds were most susceptible to erythromycin.…”
Section: Discussioncontrasting
confidence: 99%
“…(96/284). This study had high prevalence compared to studies conducted at Dessie (22.7%) [11], Rwanda (19.3%) [12], and Nigeria (17.6%) [13] Prevalence of ESBLs producers within the Enterobacteriaceae in the study was 41.7%. This finding is consistent with similar studies carried out at Jimma University Specialized Hospital (38.4%) [14], in Addis Ababa (50.7%) [15], in Nigeria (47.1%) [16] and in India (38.2%) [17].…”
Section: Discussionmentioning
confidence: 54%